LITERATURE REVIEW: THE RELATIONSHIP OF THE USE OF SOCIAL MEDIA TO THE INCIDENCE OF ANXIETY IN ADOLESCENTS IN INDONESIA - Indah Ayu Afsari; Syifaul Lailiyah; Mohammad Zainal Fatah (Lembaga Penelitian dan Terapan untuk Kesehatan Jiwa (Lenterakaji), 2023)
Background: Social media is an example of technological advances. Social media users can experience social media addiction due to the high usage. Adolescents who are socially addicted have a higher potential for experiencing social anxiety disorder or anxiety. Purpose: This literature review study was to examine the relationship between social media use and anxiety disorders in adolescents in Indonesia. Methods: This research was a systematic review by searching articles using the Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) method. Inclusion criteria included articles with cross-sectional research with research subjects on adolescents in Indonesia, full text, and according to keywords. This study used articles of national standard with an article search database, namely Google Schoolar. Results: Based on the six articles that have been analyzed, there was a relationship between the frequency of anxiety of adolescents who use social media in Indonesia and the intensity of their use. Conclusion: Several factors have contributed to the high use of social media, including many interesting online features and games, the COVID-19 pandemic so that all activities were carried out online, and a sense of not wanting to be left behind by trends among teenagers. Abstrak Latar Belakang: Media sosial merupakan salah satu contoh dari kemajuan teknologi. Pengguna media sosial dapat megalami kecanduan media sosial karena tingginya penggunaan. Remaja yang kecanduan sosial memiliki potensi lebih tinggi untuk mengalami gangguan kecemasan sosial atau anxiety. Tujuan: studi literature review ini adalah untuk mengkaji mengenai hubungan antara penggunaan media sosial dengan gangguan kecemasan pada remaja di Indonesia. Metode: penelitian ini adalah tinjauan sistematis dengan penelusuran artikel menggunakan metode Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA). Kriteria inklusi meliputi artikel dengan penelitian cross-sectional dengan subjek penelitian remaja di Indonesia, full text, dan sesuai dengan kata kunci. Penelitian ini menggunakan artikel bertaraf nasional dengan database pencarian artikel yaitu google schoolar. Hasil: Berdasarkan enam artikel yang telah dianalisis terdapat hubungan antara frekuensi kecemasan remaja pengguna media sosial di Indonesia dengan intensitas penggunaannya. Kesimpulan: Beberapa faktor yang mendorong tingginya penggunaan media sosial antara lain banyaknya fitur dan game online yang menarik, adanya pandemi COVID-19 sehingga semua aktivitas dilakukan secara online, serta adanya rasa tidak ingin ketinggalan trend di kalangan remaja.